Designing and Validating a Questionnaire for the Assessment of Staff Satisfaction with Occupational Health, Safety, and Environmental Management System Status - Rohollah Fallah Madvari (Muhandisī-i bihdāsht-i ḥirfah/ī, 2020)
Background and Objective: Currently, due to the development of urbanization and growth of industrial units, the issues of health, safety, and environment are more important. The present study aimed to design and validate a tool for the assessment of staff satisfaction with occupational health, safety, and environmental management system (HSE-MS) status due to the lack of a standard questionnaire in this regard. Materials and Methods: In this study, an initial questionnaire, including 60 items, was designed with the help of scientific resources and expert opinions. Then, the opinions of 12 experts in occupational health, safety, and environment were used to standardize and validate the assessment questionnaire. Content validity index (CVI) and content validity ratio (CVR) were utilized to validate the questionnaire. Cronbach's alpha was used to evaluate the reliability of the questionnaire, and Pearson's correlation coefficient was utilized to assess the correlation between questionnaire scales. Moreover, Kaiser-Meyer-Olkin (KMO) and Bartlett's tests were applied for the determination of factor loadings. Results: The CVI and CVR of the questionnaire were calculated at 0.88 and 0.83, respectively. Furthermore, the internal consistency and reproducibility of the designed questionnaire were confirmed according to Cronbach's alpha coefficient (0.80). In addition, the results of Bartlett's test showed that there was a significant correlation between the variables, and the KMO value was reported as 0.840. Conclusion: The obtained results of this study showed that the CVI and CVR of the designed questionnaire were higher than the standard values of 0.79 and 0.55, respectively. The obtained Cronbach's alpha coefficient also indicated the strong internal consistency of the questionnaire. Therefore, the designed questionnaire for the assessment of staff satisfaction with occupational HSE-MS status can be useful in present industries with regard to acceptable validity and reliability.